MR and CT Imaging Spectrum of Right-Sided Cardiac Masses: A Pictorial Essay - Murugan, MK; Gulati, GS (Nepalese Journal of Radiology, 2013)
Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 96-110 DOI: http://dx.doi.org/10.3126/njr.v2i2.7695